Related Relations between kinematic variables and free landing Corner with Air movements skillfully rear airbag horizontal bar in gymnastics - Abdul Slam Abdul Razzaq, Zinah; Mahohammed Sayah, Qasim (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to verify the relationship between the variables of the kinematics liberation corner turn-on device where the players need to corner of gymnastics free occasion so they can complete successfully axle and landing correctly. This study chose 11 players who participated in the 2018 Iraq club championship that was held in Baghdad and analyzed the best performance in the competition. The camera used for (Sony HDR-200 frequency 60 Mbps) after turning photography picture Register to Kinovea program (8.25) for the purpose of extracting the digital data and then treated statistically using the correlation coefficient and decadence pace using the statistical program Spss 19). Liberalization has been the appointment of an independent variable angle of kinematic variables belonging to verify the difference of each factor. The level of significance was set at p